Anxiety and depression in patients with rheumatoid arthritis - Isik, Ahmet; Koca, Suleyman Serdar; Ozturk, Abdullah; Mermi, Osman (Springer London Ltd, 2007)
Rheumatoid arthritis (RA) mostly follows a painful, progressively disabling course, and individuals with RA experience more psychological distress than healthy individuals. The objective of the present study is to examine the prevalences of accompanying anxiety and depression in RA cases. The study included 82 RA cases and 41 age- and sex-matched healthy volunteers as the control group. Psychiatric examinations of all cases of the patient and control groups were performed according to DSM-IV criteria. Hamilton Anxiety Scale or Hamilton Depression Scale was applied to those who were found to have anxiety or depression. Total prevalence of anxiety, depression, and mixed anxiety-depressive disorder was found to be 70.8% (n=58) in the patient group and 7.3% (n=3) in the control group, and the difference was significant (p < 0.001). Of the RA patients, 41.5% (n=34) was found to have depression, 13.4% (n=11) anxiety, and 15.9% (n=13) mixed anxiety-depressive disorder. The disease duration in patients with anxiety was shorter than the RA patient with depression (p < 0.05). The disease duration was positively correlated with the degree of depression and negatively correlated with the degree of anxiety (r=0.341, p < 0.05; r=-0.642, p < 0.05, respectively). The results of our study suggest that prevalences of anxiety and mainly depression, increase in RA cases. When the clinical picture in RA cases becomes complicated with anxiety or depression, some problems at patients' adaptation and response to treatment may be possible. RA cases should be monitored for accompanying anxiety or depression during follow-up.
Keywords: anxiety; depression; rheumatoid arthritis